2005
DOI: 10.1103/physrevd.72.124008
|View full text |Cite
|
Sign up to set email alerts
|

Integrability of particle motion and scalar field propagation in Kerr-(anti-) de Sitter black hole spacetimes in all dimensions

Abstract: We study the Hamilton-Jacobi and massive Klein-Gordon equations in the general Kerr-(Anti) de Sitter black hole background in all dimensions. Complete separation of both equations is carried out in cases when there are two sets of equal black hole rotation parameters.We analyze explicitly the symmetry properties of these backgrounds that allow for this Liouville integrability and construct a nontrivial irreducible Killing tensor associated with the enlarged symmetry group which permits separation. We also deri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Later it was shown that 5D results can be extended to an arbitrary number of dimensions, provided that rotation parameters of the MP metric can be divided into two classes, and within each of the classes these parameters are equal of one another [228]. Similar results were found in the presence of the cosmological constant and NUT parameters [163], [229], [156], [227], [225], [40], [59], [226]. It was also demonstrated that a stationary string configuration in the 5D Myers-Perry spacetime is completely integrable [79].…”
Section: Hidden Symmetries In Higher Dimensionssupporting
confidence: 70%
“…Later it was shown that 5D results can be extended to an arbitrary number of dimensions, provided that rotation parameters of the MP metric can be divided into two classes, and within each of the classes these parameters are equal of one another [228]. Similar results were found in the presence of the cosmological constant and NUT parameters [163], [229], [156], [227], [225], [40], [59], [226]. It was also demonstrated that a stationary string configuration in the 5D Myers-Perry spacetime is completely integrable [79].…”
Section: Hidden Symmetries In Higher Dimensionssupporting
confidence: 70%
“…Higher dimensional, asymptotically flat, Kerr black holes were first found in [2] and the asymptotically (A)dS analogues were found more recently in [3]. The five-dimensional Myers-Perry and Kerr-(A)dS black holes were shown to possess Killing tensors for arbitrary rotation parameters in [4] and [5] respectively, and in the case where the rotation parameters can take one of two different values, a Killing tensor has been found in all dimensions [6].…”
Section: Introductionmentioning
confidence: 97%
“…Secondly, this equation can be reduced to ODEs governing the radial and angular behaviour by separation of variables. It is known that this separability property of the Kerr metric does extend to some of the higher-dimensional MP metrics [17,18,19], and MP metrics with a cosmological constant [20]. This makes the study of scalar field perturbations in such backgrounds tractable.…”
Section: Introductionmentioning
confidence: 98%